Moses among the Greek lawgivers: reading Josephus' antiquities through Plutarch's lives - Westwood, Ursula (Journal for the study of Judaism, 2023)
Josephus' Antiquities invites his audience to compare the Jewish lawgiver, Moses, with the famous legislators of Greece and Rome. This book responds to the invitation, using Plutarch's Lives to uncover a series of appeals and challenges embedded in Josephus' narrative.